1997
DOI: 10.1177/019874299702200203
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Choice and Task Preference on the Work Performance of Students with Behavior Problems

Abstract: This investigation compared the effects of choice and assignment of preferred and nonpreferred tasks on the work performance of three students with moderate intellectual impairments and challenging behavior in a classroom setting. After assessing student task preferences, a multielement design was used to evaluate three conditions: (a) assigning a preferred task, (b) assigning a nonpreferred task, and (c) providing a choice between work tasks. Results indicated individual participant data were idiosyncratic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 14 publications
1
34
0
Order By: Relevance
“…Similar findings were reported by Cole, Davenport, Bambara, and Ager (1997). The authors of both of these studies concluded that assigning a preferred task is as effective as allowing the participant to choose among preferred and nonpreferred tasks.…”
Section: Differential Effects Of Choicesupporting
confidence: 79%
See 1 more Smart Citation
“…Similar findings were reported by Cole, Davenport, Bambara, and Ager (1997). The authors of both of these studies concluded that assigning a preferred task is as effective as allowing the participant to choose among preferred and nonpreferred tasks.…”
Section: Differential Effects Of Choicesupporting
confidence: 79%
“…Although Parsons et al (1990) and Cole et al (1997) showed that choice and preference produced equivalent effects on on-task behavior, results from Bambara, Ager, and Koger (1994) are equivocal. In their study, five participants with mental retardation were given a choice between tasks or were assigned a task.…”
Section: Differential Effects Of Choicementioning
confidence: 99%
“…• EBD and another disability specified in IDEA (e.g., learning disability, other health impairment, speech and language disorder), except for students with a dual diagnosis of moderate mental retardation or developmental disabilities (e.g.. Cole, Davenport, Bambara, & Ager, 1997;O'Reilly et al, 2002) as these students typically participate In a functional skills curricula rather than traditional core curricula (Heckaman et al, 2000;Lane et al, 1999).…”
Section: Inclusion Criteriamentioning
confidence: 99%
“…Preference, on the other hand, promotes engagement in activities that are more reinforcing or liked by the child (Morgan, 2006). Research has found no differences in the effects of teacher or student selected tasks (Cole, Davenport, Bambara, & Ager, 1997). In the classroom, teachers can seek to learn student's favorite learning activities and incorporate these preferences into lessons and assessments (Vaughn & Horner, 1997).…”
Section: Desirable Tasksmentioning
confidence: 99%
“…Research has found that preference has a greater effect on behavior and engagement than choice making. However, there is a positive effect of choice making when the choice is between low-preference items (Cole et al, 1997;Killu, Clare, & Im, 1999;Umbreit & Blair, 1996). In addition, the function of the behavior moderates the effects of choice making for students (Romaniuk et al, 2002).…”
Section: Desirable Tasksmentioning
confidence: 99%